Preparation method of magnesium salt induced coupling carbonization curing carbon nitride attached cement-based material
By using magnesium salt-induced carbonization curing, a stable carbon nitride bridging structure is formed on the surface of cement-based materials, which solves the problem of photocatalysts being encapsulated by binders, improves the aging resistance and wear resistance of the photocatalytic layer, and enhances the purification efficiency.
Patent Information
- Application Number
- CN202411498331.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In existing photocatalytic cement-based materials, the photocatalyst has low purification efficiency due to the encapsulation of the binder, and the binder has poor aging resistance, making it unable to effectively purify pollutants in the long term.
The magnesium salt-induced coupled carbonation curing method combines positively charged magnesium ions with colloidal carbon nitride, and generates magnesium carbonate through carbonation curing to bridge adjacent carbon nitride and cement matrix, forming a stable three-dimensional bridging structure and avoiding the shielding of photocatalyst.
It improves the aging and wear resistance of the photocatalytic layer, enhances the stability of photocatalytic purification efficiency, and reduces material costs.
Smart Images

Figure CN119285375A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental materials, and in particular relates to a method for preparing a carbon nitride-attached cement-based material induced by magnesium salt and coupled with carbonization curing. Background Art
[0002] With the impact of global warming and the acceleration of urbanization, the paved area and building density of cities are increasing, causing the increase of ground rainwater runoff. The pollution caused by heavy metal ions, suspended solids and organic matter in rainwater is becoming more and more serious. In particular, the heavy metal ions and organic pollutants in the stagnant water remain on the ground, which will increase the concentration of road pollutants. The odor and volatile organic matter emitted by rainwater will also pollute the air. In addition, the exhaust gas emitted by cars on the road contains nitrogen oxides (NO x ) will lead to a sharp deterioration in air quality. Therefore, the purification of rainwater runoff pollution and NO x The prevention and control of exhaust gas pollution is imminent. Combining green and sustainable photocatalytic environmental remediation technology with cement-based pavement materials and developing new cement-based pavement materials with rainwater and exhaust gas purification functions is considered to be one of the most promising green means to purify rainwater runoff pollution and exhaust gas.
[0003] At present, the research on photocatalytic cement-based materials is mostly focused on constructing photocatalytic coatings on their surfaces. For example, patent CN115180976A discloses a method for preparing photocatalytic cement-based materials; patent CN 116920831A discloses a VOCs decomposition photocatalyst coating and its preparation method and application; patent CN 116673074A discloses a titanium dioxide photocatalytic coating and its preparation method and product; patent CN 114308123A discloses a photocatalytic coating material and its preparation method. At the same time, in order to ensure the stable adhesion of the photocatalyst on the cement matrix, existing studies often use a binder and a photocatalyst to evenly mix to prepare a photocatalytic coating, but this will cause the photocatalyst to be wrapped by the binder and unable to fully contact the target pollutants and light, resulting in very limited purification efficiency. In addition, organic binders have shortcomings such as poor aging resistance and weak mechanical properties, and cannot maintain long-term effective purification functions. Therefore, exploring a stable attachment strategy for photocatalysts without the assistance of binders has become the key to maximizing the purification efficiency and long-term purification performance of photocatalytic cement-based materials. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a magnesium salt-induced coupled carbonization-cured carbon nitride-attached cement-based material, which uses positively charged magnesium ions to compound negatively charged colloidal carbon nitride and sprays it on the surface of the cement-based material. The magnesium ions are converted into magnesium carbonate through carbonization curing, so that the magnesium carbonate is used to bridge the adjacent carbon nitride and cement matrix to form a stable three-dimensional bridging structure. It not only overcomes the problem of photocatalyst shielding caused by traditional binder mixing, but also greatly improves the aging resistance and wear resistance of the photocatalytic layer and reduces the material cost.
[0005] To achieve the above object, the present invention adopts the following technical solution: A magnesium salt induced coupled carbonization cured carbon nitride adhered cement-based material, the preparation method of which comprises the following steps: (1) dispersing carbon nitride powder in a sodium hydroxide solution at 80±2°C, stirring with a magnetic stirrer and centrifuging, dispersing the precipitate in deionized water to obtain a colloidal carbon nitride dispersion; (2) Under a protective atmosphere, dissolving a soluble magnesium salt in the colloidal carbon nitride dispersion obtained in step 1) by magnetic stirring to obtain a dispersion containing magnesium salt and colloidal carbon nitride; (3) After removing the calcium carbonate layer on the surface of the hardened cement-based material, the dispersion containing magnesium salt and colloidal carbon nitride obtained in step (2) is sprayed on the surface of the hardened cement-based material, and then carbonization curing is performed to obtain a cement-based material with stably attached carbon nitride.
[0006] Furthermore, the carbon nitride powder in step (1) is specifically graphite phase carbon nitride powder, which has a two-dimensional layered morphology, a thickness of 20-50 nm, a particle size of 0.3-0.5 μm, and a surface Zeta potential of -15--25 mV.
[0007] Furthermore, the mass concentration of the sodium hydroxide solution in step (1) is 0.5-0.7%.
[0008] Furthermore, in step (1), the amount of carbon nitride powder added to the sodium hydroxide solution is 1-12 g / L.
[0009] Furthermore, the rotation speed of the magnetic stirring in step (1) is 600 rpm and the time is 12 hours.
[0010] Furthermore, the centrifugal speed in step (1) is 4000 rpm and the time is 5 minutes.
[0011] Furthermore, the concentration of the dispersion of colloidal carbon nitride obtained in step (1) is 0.1-3 g / L; specifically, the colloidal carbon nitride obtained is a carbon nitride sol; wherein the carbon nitride is fibrous, has a particle size of 50-80 nm, is surface-modified with hydroxyl functional groups, and has a Zeta potential of -35-40 mV.
[0012] Furthermore, the protective atmosphere in step (2) is nitrogen with a flow rate of 100 ml / min.
[0013] Furthermore, the soluble magnesium salt in step (2) is magnesium nitrate or magnesium sulfate.
[0014] Furthermore, in step (2), the amount of soluble magnesium salt added to the colloidal carbon nitride dispersion is 7-15 g / L.
[0015] Furthermore, the hardened cement-based material in step (3) is cement paste, cement mortar or concrete with standard curing for 28 to 180 days.
[0016] Furthermore, the spraying amount of the dispersion containing magnesium salt and colloidal carbon nitride in step (3) is 0.1~1 L / m 2 .
[0017] Furthermore, the carbonization curing conditions in step (3) are: relative humidity 50-95%, carbon dioxide concentration 0.04-20%, and curing time 48 hours.
[0018] The colloidal carbon nitride in the present invention has a large electronegativity and can be evenly dispersed in an aqueous solution. The bridging nitrogen atom in its molecular structure has a lone pair of electrons that can chelate with positively charged magnesium ions in the aqueous solution, and these magnesium ions can react with carbon dioxide in a carbonization environment to form magnesium carbonate. The in-situ formed magnesium carbonate can bridge the adjacent carbon nitride and the hydrated calcium silicate on the surface of the cement matrix, and form a three-dimensional spatial structure (such as Figure 1 ), thereby consolidating the carbon nitride on the surface of the cement matrix.
[0019] The present invention has the following advantages: Compared with the traditional photocatalytic layer prepared with a binder, the present invention uses positively charged magnesium ions to combine with colloidal carbon nitride through electrostatic action and the magnesium carbonate generated in situ through carbonization curing not only does not wrap the active sites on the edge of carbon nitride, but the three-dimensional bridging structure composed of magnesium carbonate can effectively increase the exposure of the active sites of carbon nitride. The in-situ generated magnesium carbonate not only has better compatibility with the cement matrix, but also can improve the aging resistance and wear resistance of cement-based materials, greatly improving the stability of its long-term photocatalytic purification effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of the composite spatial structure of carbon nitride and magnesium carbonate.
[0021] Figure 2 NO xSchematic diagram of the photocatalytic performance test system, including: ① high-purity air; ② pressure reducing valve; ③ steady flow valve; ④ NO cylinder gas; ⑤ gas washing bottle; ⑥ flow rate controller; ⑦ temperature and humidity sensor; ⑧ reactor; ⑨ NO x Analyzer;⑩Tail gas absorption bottle.
[0022] Figure 3 The sample comparison diagram of the carbon nitride-attached cement-based material prepared in Example (left) and Comparative Example 1 (right) after ultrasonic cleaning experiment. As can be seen from the figure, after ultrasonic cleaning, the carbon nitride-attached cement-based material prepared in Comparative Example 1 without adding magnesium salt has almost completely lost carbon nitride, exposing the gray-white cement matrix. DETAILED DESCRIPTION
[0023] The preparation of a magnesium salt induced coupled carbonization cured carbon nitride adhered cement-based material comprises the following steps: (1) Dispersing carbon nitride powder in an amount of 1-12 g / L in a sodium hydroxide solution at 80±2°C and a mass concentration of 0.5-0.7%, stirring magnetically at 600 rpm for 12 hours, centrifuging at 4000 rpm for 5 minutes, taking the precipitate and dispersing it in deionized water by magnetic stirring to obtain a colloidal carbon nitride dispersion with a concentration of 0.1-3 g / L; (2) dissolving a soluble magnesium salt in an amount of 7 to 15 g / L in the colloidal carbon nitride dispersion obtained in step 1) by magnetic stirring under nitrogen at a flow rate of 100 ml / min to obtain a dispersion containing magnesium salt and colloidal carbon nitride; (3) After removing the surface calcium carbonate layer of the hardened cement-based material with a grinding and polishing machine, press 0.1~1 L / m 2 The dispersion containing magnesium salt and colloidal carbon nitride obtained in step (2) is sprayed in an amount of , and then moved into a carbonization box and cured for 48 hours under the conditions of relative humidity of 50-95% and carbon dioxide concentration of 0.04-20%, thereby obtaining a cement-based material with stably attached carbon nitride.
[0024] The carbon nitride powder in step (1) is specifically graphite phase carbon nitride powder, which has a two-dimensional layered morphology, a thickness of 20-50 nm, a particle size of 0.3-0.5 μm, and a surface Zeta potential of -15--25 mV.
[0025] The soluble magnesium salt in step (2) is magnesium nitrate or magnesium sulfate.
[0026] The hardened cement-based material in step (3) is cement paste, cement mortar or concrete with standard curing for 28 to 180 days.
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0028] The carbon nitride powder used in the embodiment is specifically graphite phase carbon nitride powder, which has a two-dimensional layered morphology, a thickness of 20-50 nm, a particle size of 0.3-0.5 μm, and a surface Zeta potential of -15--25 mV. Example
[0029] This embodiment adopts magnesium salt induced coupled carbonization curing to prepare colloidal carbon nitride attached cement-based material, and its specific preparation steps are as follows: Take 0.5g of carbon nitride powder and disperse it in 200mL of sodium hydroxide solution (80℃, mass fraction of sodium hydroxide is 0.5 wt%) by magnetic stirring (600 rpm), keep stirring for 12 hours and centrifuge for 5 minutes (4000 rpm), take the precipitate and disperse it in 300mL of deionized water to obtain a dispersion of colloidal carbon nitride with a concentration of 0.5 g / L. Take 3.5g of magnesium nitrate and dissolve it in the above-mentioned dispersion of colloidal carbon nitride by magnetic stirring, and pass nitrogen at a flow rate of 100 ml / min to obtain a dispersion containing magnesium salt and colloidal carbon nitride. Take the cement slurry that has been cured for 28 days, remove the surface carbonized layer with a grinder and polisher, and then spray the dispersion containing magnesium salt and colloidal carbon nitride on its surface, and control the spraying amount to 0.5 L / m 2 , and then moved into a carbonization box, and the carbonization conditions were controlled to be 70% relative humidity and 15% carbon dioxide concentration. After curing for 48 hours, a photocatalytic cement-based material with stably attached colloidal carbon nitride was obtained.
[0030] In order to simulate the scenarios of rain erosion, mechanical wear and UV aging that may be encountered in actual applications, ultrasonic cleaning experiments, wear experiments and accelerated aging experiments were set up respectively. Specifically, the obtained photocatalytic cement-based material specimens (1) were ultrasonically cleaned in a CNC ultrasonic cleaner at a power of 40 watts for 1 minute to simulate the effect of rain erosion; (2) the obtained photocatalytic cement-based material specimens were polished with a grinder at a power of 500 watts for 2 minutes, with a grinding wheel of 36 meshes, to simulate the effect of mechanical wear; (3) the obtained photocatalytic cement-based material specimens were placed in an aging box and irradiated with a xenon lamp light source with an intensity of 1200W / m 2 , accelerated aging for 15 days in an environment with a blackboard temperature of 60°C and a humidity of 60% to simulate UV aging.
[0031] After the above test blocks were cleaned and dried naturally, the photocatalytic gas purification experiment was carried out. Figure 2NO x Photocatalytic performance test system: The whole test system is a closed space, with nitric oxide as the simulated air pollutant, the target gas concentration is controlled to be 1 ppm NO through the gas mixing device, the gas flow rate is 1 L / min, the humidity is 50±2%, the temperature is 25±2℃, the reactor is filled with concrete samples (Φ30 mm×15 mm), and a fluorescent lamp (wavelength>420nm) is installed 10 mm above the reactor. The gas passing through the reactor directly enters the NO x The analyzer collects NO in the gas in real time x The photocatalytic efficiency of photocatalytic steel slag exposed concrete is calculated according to the following formula: , Where ƞ is the photocatalytic efficiency (%), C off is the NO concentration when the light is not on, C on is the NO concentration when the light is on.
[0032] The results show that the photocatalytic gas purification efficiency of the material was 65% and 61% before and after the ultrasonic cleaning experiment; the photocatalytic gas purification efficiency of the material was 65% and 50% before and after the mechanical friction experiment; and the photocatalytic gas purification efficiency of the material was 65% and 60% before and after the accelerated aging experiment.
[0033] Comparative Example 1 The concrete preparation steps of the colloidal carbon nitride-attached cement-based material prepared in this comparative example without adding magnesium salt are as follows: Take 0.5g of carbon nitride powder and disperse it in 200mL of sodium hydroxide solution (80℃, mass fraction of sodium hydroxide is 0.5 wt%) by magnetic stirring (600 rpm), keep stirring for 12 hours and centrifuge for 5 minutes (4000 rpm), take the precipitate and disperse it in 300mL of deionized water, and pass nitrogen at a flow rate of 100 ml / min to obtain a dispersion of colloidal carbon nitride with a concentration of 0.5 g / L. Take the cement slurry that has been cured for 28 days, remove the surface carbonized layer with a grinder, and then spray the dispersion containing colloidal carbon nitride on its surface, and control the spraying amount to 0.5 L / m 2 , and then moved into a carbonization box, the carbonization conditions were controlled to be 70% relative humidity and 15% carbon dioxide concentration, and after curing for 48 hours, a photocatalytic cement-based material with colloidal carbon nitride attached was obtained.
[0034] The experiment was carried out according to the method described in the embodiment. The results showed that the photocatalytic gas purification efficiency of the material was 65% and 5% before and after the ultrasonic cleaning experiment; the photocatalytic gas purification efficiency of the material was 65% and 10% before and after the mechanical friction experiment; and the photocatalytic gas purification efficiency of the material was 65% and 20% before and after the accelerated aging experiment.
[0035] From the comparison of the experimental results of the embodiment and the comparative example 1, it can be seen that whether the colloidal carbon nitride is compounded with magnesium ions is one of the key factors for its stable adhesion on the cement matrix. In a carbon dioxide environment, magnesium ions are carbonized to form stable magnesium carbonate, which can bridge the adjacent carbon nitride and cement matrix to form a stable three-dimensional bridging structure to ensure the stable adhesion of carbon nitride on the surface of the cement matrix.
[0036] Comparative Example 2 This comparative example does not use carbonization curing to prepare the cement-based material with colloidal carbon nitride attached, and the specific preparation steps are as follows: Take 0.5g of carbon nitride powder and disperse it in 200mL of sodium hydroxide solution (80℃, mass fraction of sodium hydroxide is 0.5 wt%) by magnetic stirring (600 rpm), keep stirring for 12 hours and centrifuge for 5 minutes (4000 rpm), take the precipitate and disperse it in 300mL of deionized water to obtain a dispersion of colloidal carbon nitride with a concentration of 0.5 g / L. Take 3.5g of magnesium nitrate and dissolve it in the above-mentioned dispersion of colloidal carbon nitride by magnetic stirring, and pass nitrogen at a flow rate of 100 ml / min to obtain a dispersion containing magnesium salt and colloidal carbon nitride. Take cement mortar that has been cured for 28 days, remove the surface carbonized layer with a grinder and polisher, and then spray the dispersion containing magnesium salt and colloidal carbon nitride on its surface, and control the spraying amount to 0.5 L / m 2 Then, after curing for 48 hours at room temperature (50% relative humidity, 25°C), a photocatalytic cement-based material with colloidal carbon nitride attached was obtained.
[0037] The experiment was carried out according to the method described in the embodiment. The results showed that the photocatalytic gas purification efficiency of the material was 65% and 12% before and after the ultrasonic cleaning experiment; the photocatalytic gas purification efficiency of the material was 65% and 13% before and after the mechanical friction experiment; and the photocatalytic gas purification efficiency of the material was 65% and 22% before and after the accelerated aging experiment.
[0038] Comparison of the experimental results of the embodiment with those of comparative example 2 shows that carbonation curing is another key factor for magnesium salt to induce stable attachment of carbon nitride on the surface of cement matrix, which can provide sufficient carbon dioxide for magnesium ions to react to form magnesium carbonate, and magnesium carbonate is not only a key component for bridging adjacent carbon nitrides, but also a bridging component for carbon nitride and calcium silicate hydrate in cement matrix. However, in an air environment with low carbon dioxide concentration, only magnesium carbonate with low crystallinity can be formed, which cannot play a role in firmly embedding carbon nitride.
[0039] Comparative Example 3 In this comparative example, magnesium salt and carbon nitride powder are directly (grinded) mixed to form a dispersion, and carbonization and curing are performed to prepare a cement-based material with carbon nitride attached. The specific preparation steps are as follows: 0.5 g of carbon nitride powder and 3.5 g of magnesium nitrate were ground and mixed evenly, and then dispersed in 300 mL of deionized water by magnetic stirring (600 rpm), and nitrogen was introduced at a flow rate of 100 ml / min to obtain a dispersion containing magnesium salt and carbon nitride. Take the cement mortar that has been cured for 28 days, remove the surface carbonized layer with a grinder, and then spray the dispersion containing magnesium salt and carbon nitride on its surface, and control the spraying amount to 0.5 L / m 2 , and then moved into a carbonization box, and the carbonization conditions were controlled to be 70% relative humidity and 15% carbon dioxide concentration. After curing for 48 hours, a photocatalytic cement-based material with attached carbon nitride was obtained.
[0040] The experiment was carried out according to the method described in the embodiment. The results showed that the photocatalytic gas purification efficiency of the material was 35% and 8% before and after the ultrasonic cleaning experiment; the photocatalytic gas purification efficiency of the material was 35% and 9% before and after the mechanical friction experiment; and the photocatalytic gas purification efficiency of the material was 35% and 15% before and after the accelerated aging experiment.
[0041] From the comparison of the experimental results of the embodiment and comparative example 3, it can be seen that whether carbon nitride can be evenly combined with magnesium ions is also one of the key factors for whether carbon nitride can be stably attached to the surface of the cement matrix. Ordinary carbon nitride powder is easy to agglomerate into clusters in aqueous solution due to its large surface energy and low Zeta potential, and it is difficult to fully expose its surface chelating sites with magnesium ions, and it is also impossible to form a uniform and stable carbon nitride dispersion. Therefore, although it can form magnesium carbonate during the carbonization curing process, it cannot effectively bridge adjacent carbon nitride and cement matrix. At the same time, the agglomerated carbon nitride particles greatly reduce the exposure rate of their active sites, thereby reducing the photocatalytic purification efficiency.
[0042] The applicant declares that the present invention illustrates the detailed composition and method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed composition and method, that is, it does not mean that the present invention must rely on the above-mentioned detailed composition and method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a magnesium salt induced coupled carbonization cured carbon nitride adhered cement-based material, characterized in that: The steps include: (1) dispersing carbon nitride powder in a sodium hydroxide solution at 80±2°C, stirring with a magnetic stirrer and centrifuging, dispersing the precipitate in deionized water to obtain a colloidal carbon nitride dispersion; (2) Under a protective atmosphere, dissolving a soluble magnesium salt in the colloidal carbon nitride dispersion obtained in step 1) by magnetic stirring to obtain a dispersion containing magnesium salt and colloidal carbon nitride; (3) After removing the calcium carbonate layer on the surface of the hardened cement-based material, the dispersion containing magnesium salt and colloidal carbon nitride obtained in step (2) is sprayed on the surface of the hardened cement-based material, and then carbonization curing is performed to obtain a cement-based material with stably attached carbon nitride.
2. The preparation method according to claim 1, characterized in that: The carbon nitride powder in step (1) is specifically graphite phase carbon nitride powder; the mass concentration of the sodium hydroxide solution is 0.5-0.7%; and the amount of carbon nitride powder added to the sodium hydroxide solution is 1-12 g / L.
3. The preparation method according to claim 1, characterized in that: The speed of the magnetic stirring in step (1) is 600 rpm for 12 hours; the speed of the centrifugation is 4000 rpm for 5 minutes.
4. The preparation method according to claim 1, characterized in that: The concentration of the colloidal carbon nitride dispersion obtained in step (1) is 0.1-3 g / L.
5. The preparation method according to claim 1, characterized in that: The protective atmosphere in step (2) is nitrogen with a flow rate of 100 ml / min.
6. The preparation method according to claim 1, characterized in that: The soluble magnesium salt in step (2) is magnesium nitrate or magnesium sulfate; the amount added to the colloidal carbon nitride dispersion is 7-15 g / L.
7. The preparation method according to claim 1, characterized in that: The hardened cement-based material in step (3) is cement paste, cement mortar or concrete with standard curing for 28 to 180 days.
8. The preparation method according to claim 1, characterized in that The spraying amount of the dispersion containing magnesium salt and colloidal carbon nitride in step (3) is 0.1~1 L / m 2 .
9. The preparation method according to claim 1, characterized in that: The carbonization curing conditions in step (3) are: relative humidity 50-95%, carbon dioxide concentration 0.04-20%, and curing time 48 hours.
10. A cement-based material with carbon nitride stably attached to the surface prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon nitride-loaded photocatalytic cement-based material and preparation method thereof
CN114904553A
Preparation method of photocatalytic cement-based material
CN115180976A
Pervious concrete capable of efficiently and continuously purifying sewage
CN116514487A
A cementitious composition with photocatalytic activity
WO2020127559A1